PENGARUH ENTREPRENEURIAL LEADERSHIP DAN WORK LIFE BALANCE TERHADAP KINERJA MELALUI INOVASI SAAT WORK FROM HOME - Fandi Fatoni; Nurul Indawati; Ec. Budiono; Anang Kistyanto; Andre D. Witjaksono (ILIN Institute, 2021)
The purpose of this study was to determine the effect of entrepreneurial leadership and work life balance on innovation and performance through innovation at the Lecturers of the Faculty of Economics, State University of Surabaya during work from home. This type of research is quantitative research. The research location was conducted at the Faculty of Economics, State University of Surabaya. The population used is 112 lecturers at the Faculty of Economics, State University of Surabaya and the sample size collected was 74 respondents. The data analysis technique was carried out with a Structural Equation Model (SEM) approach using the Patrial Least Square (PLS) analysis method supported by the smartPLS 3.0 computer software. The results of this study state that entrepreneurial leadership has an insignificant influence on lecturer innovation, entrepreneurial leadership has no significant effect on lecturer performance, work life balance has a significant effect on innovation, work life balance has a significant effect on lecturer performance, lecturer innovation has a significant and positive effect. on lecturer performance, entrepreneurial leadership has no significant effect on lecturer performance intervening by lecturer innovation, work life balance has a significant effect on lecturer performance intervening by lecturer innovation.